Anticancer Therapy: Light‐Activated Hypoxia‐Responsive Nanocarriers for Enhanced Anticancer Therapy (Adv. Mater. 17/2016). Issue 17 (May 2016) - Qian, Chenggen; Yu, Jicheng; Chen, Yulei; Hu, Quanyin; Xiao, Xuanzhong; Sun, Wujin; Wang, Chao; Feng, Peijian; Shen, Qun‐Dong; Gu, Zhen
Abstract : A light‐activated hypoxia‐responsive drug‐delivery vehicle is described by Q.‐D. Shen, Z. Gu, and co‐workers on page 3313. This conjugated‐polymer‐based nanocarrier can be activated by photoirradiation, producing singlet oxygen ( 1 O2 ) and inducing hypoxia to promote release of its cargo inside tumor cells for enhanced anticancer efficacy.